Segunyeng Sebagai Sarana Komunikasi Lintas Budaya Dalam Perspektif Kisah Para Rasul 4: 32-37 - Harming; Krismadayanti (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The purpose of writing this article is to analyze sequnyeng as a form of cross-cultural communication from the perspective of Acts 4:32-37. The writing method used is a qualitative method with a literature study approach to find data about the culture of the Oma Lung Dayak tribe. Methods The hermeneutic approach is used to investigate, study and discuss the text of Acts 4:32-37 carefully with the aim of finding the meaning contained in the text. The conclusion of "sequnyeng as a form of cross-cultural communication in the perspective of Acts 4:32-37" in theoretical implications is First, sequnyeng is a mutual cooperation activity carried out by the Oma Lung Dayak people when they do heavy work. In these activities the community builds cross-cultural communication verbally and non-verbally through togetherness and sharing. Second, the early church in Acts 4:32-37 were people who believed in Jesus, they had a lifestyle of fellowship in love. The fellowship is a manifestation of togetherness where they always live by prioritizing others besides that they share by witnessing and telling about their experiences of faith in Jesus and encouraging one another, affirming one another and praying for one another.